Carbonate platform drowning caught in the act: The sedimentology of Saya de Malha Bank (Indian Ocean). Issue 1 (21st September 2022) - Betzler, Christian; Lindhorst, Sebastian; Reijmer, John J. G.; Braga, Juan Carlos; Lüdmann, Thomas; Bialik, Or M.; Reolid, Jesus; Geßner, Anna‐Lena; Hainbucher, Dagmar; Bissessur, Dass
Abstract: Mesophotic reefs, hardgrounds and current‐controlled pelagic to hemipelagic carbonates are facies marking carbonate platform drowning successions, irrespective of the factors controlling this evolution. A modern analogue of a carbonate platform in a state of drowning, where these facies occur has not been properly reported on to date. In the present study, the sedimentary environments of the Saya de Malha Bank are characterized using a multi‐disciplinary approach including sedimentology, hydroacoustics, seismics and oceanography. The Saya de Malha Bank edifice with a surface of 40 808 km 2 is located in the tropical Indian Ocean and lies in a water depth of 8 to 300 m extending from the surrounding more than 2000 m deep ocean floor, with no reef reaching the sea surface. Mesophotic coral and red algal facies co‐exist with hemipelagic and bioclastic sands, together with a hardground. Ocean currents and internal waves are identified as major sedimentological controlling factors in the absence of elevated nutrient influx. Many features distributed along the present‐day Saya de Malha Bank were described from studies presenting fossil examples of carbonate platform drowning. The results herein can therefore be applied to other drowning examples, in some cases allowing for more accurate interpretation of the stratigraphic record.